1991
DOI: 10.1016/0270-9139(91)91413-u
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of unresectable hepatocellular carcinoma: An evaluation based on multivariate analysis of 90 cases

Abstract: A multivariate analysis of data from 90 patients with unresectable hepatocellular carcinoma was performed using Cox's regression model to identify factors possibly affecting their prognoses. Thirty-one patients underwent arterial anticancer chemotherapy, and the remaining 59 patients received transcatheter arterial embolization with anticancer agents. Four of 27 variables tested for all the patients (i.e., encapsulation [p less than 0.05], gross appearance of hepatocellular carcinoma [p less than 0.01], clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 5 publications
3
23
0
Order By: Relevance
“…Because the 3-year survival rate of patients with compensated liver cirrhosis and small untreated HCCs is only 25% (Barbara et al, 1992), the follow-up period in our study (mean 15 months, IQR 9-26) with mostly advanced HCCs was adequate. Similar to previous studies (Livraghi et al, 1995;Akashi et al, 1991), we found a good correlation between the estimated survival time and liver function or tumor stage, while histological differentiation was of marginal prognostic relevance. Furthermore, we found that patients with baseline AFP levels Ïœ100 ng/ml and no portal vein thrombosis had a significantly longer survival (Table II).…”
Section: Discussionsupporting
confidence: 77%
“…Because the 3-year survival rate of patients with compensated liver cirrhosis and small untreated HCCs is only 25% (Barbara et al, 1992), the follow-up period in our study (mean 15 months, IQR 9-26) with mostly advanced HCCs was adequate. Similar to previous studies (Livraghi et al, 1995;Akashi et al, 1991), we found a good correlation between the estimated survival time and liver function or tumor stage, while histological differentiation was of marginal prognostic relevance. Furthermore, we found that patients with baseline AFP levels Ïœ100 ng/ml and no portal vein thrombosis had a significantly longer survival (Table II).…”
Section: Discussionsupporting
confidence: 77%
“…As previously mentioned, eight patients of our series operated for HCC had antip53 serum antibodies, and at least one factor of bad prognosis as defined by the experience of different groups (Akashi et al, 1991;Yamashita et al, 1991;Bismuth et al, 1993;Ganne-CariĆœ et al, 1996). However, they all had a survival rate without recurrence significantly higher than that of the 24 patients with vascular invasion but without circulating anti-p53 antibodies (P = 0.05, logrank analysis).…”
Section: Discussionmentioning
confidence: 65%
“…The natural history of HCC complicated with macroscopic vascular invasion of the portal vein, shows a median survival time of only 9 to 10 weeks (Okada et al, 1992). Treatments with systemic chemotherapy, intra-arterial chemotherapy or radiofrequency ablation result in a dismal survival at 1 year ranging from 7% to 18% (Raul et al, 1994;Akashi et al, 1991;Poon et al, 2003). Hepatic resection remains the only option for these patients and a recent multicentric study showed that, resected patients lived longer, compared to those not treated surgically, with a five-year survival rate of 10% (Pawlik et al, 2005;Lin et al, 2007).…”
Section: Livermentioning
confidence: 99%